Pengaruh Intellectual Capital dan Struktur Modal terhadap Nilai Perusahaan - Holly, Anthony; Jao, Robert; Mardiana, Ana; Kusuma, Wilson (Jurnal Ekualisasi, 2025)
The objective of this research is to analyze the influence of intellectual capital and capital structure on firm value. This study utilizes Signalling Theory and Trade-off Theory to explain the interrelationships between the variables. The population for this study comprises manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2022. The sampling method used is purposive sampling, resulting in a sample of 28 companies with a total of 112 observations. Multiple regression analysis is employed to analyze the data, and hypothesis testing is conducted using the partial test (t-test). The results of this study indicate that intellectual capital and capital structure have a positive and significant effect on firm value. The findings also reveal that the enhancement of each factor significantly increases the firm value of manufacturing companies in Indonesia during the 2019-2022 period.